Determinants of Tax Audit Quality: Evidence from Tax Auditors in the North Jakarta Tax Office - Pahala, Indra; Hafifah, Nasution; Angganis, Radina; Mediawati, Elis; Anugrah, Surya (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024), 2024)
The inefficiency of tax audits represents a pressing issue requiring immediate attention. Developing and implementing a systematic, targeted audit strategy is critical to improving audit quality. This study differentiates itself from prior research by emphasizing a distinctive combination of auditor competence, information technology utilization, and professional experience as key determinants of tax audit quality. Focusing on a sample of 150 tax auditors from the North Jakarta Tax Service Office, the study provides localized insights into the benefits of enhancing audit quality. However, it is important to note the limited generalizability of these findings, as the sample is confined to a specific region in Indonesia. The results reveal that while professional experience exerted minimal influence, auditor competence and effective utilization of information technology substantially contributed to improved audit quality. These findings underscore the need for the Tax Service Office to prioritize the enhancement of auditor competence and the strategic adoption of technology to elevate audit standards. The proposed model serves as a practical framework for stakeholders seeking to improve tax audit quality. Nevertheless, further research is recommended to test the applicability of these findings across other regions in Indonesia to ensure broader relevance and effectiveness. Keywords : competence, utilization of ICT, experience, tax audit quality